2020
DOI: 10.1371/journal.pbio.3000612
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of collateral sensitivity to the antibiotic nitrofurantoin

Abstract: Antibiotic resistance increasingly limits the success of antibiotic treatments, and physicians require new ways to achieve efficient treatment despite resistance. Resistance mechanisms against a specific antibiotic class frequently confer increased susceptibility to other antibiotic classes, a phenomenon designated collateral sensitivity (CS). An informed switch of antibiotic may thus enable the efficient treatment of resistant strains. CS occurs in many pathogens, but the mechanisms that generate hypersuscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 42 publications
4
77
0
1
Order By: Relevance
“…It has previously been demonstrated that evolution of tolerance precedes evolution of resistance (3) and may result in cross-tolerance (26) and collateral sensitivity (27) Figure 3), consistent with the lack of tolerance response at the proteome level. Interestingly, we found colonies in tolerance assays with FOS (fosfomycin), which upon re-testing by MIC displayed an elevated level of resistance and are likely spontaneous mutants ( Supplementary Figure 4), a phenomenon frequently described for this antibiotic (29).…”
Section: Downloaded Fromsupporting
confidence: 80%
“…It has previously been demonstrated that evolution of tolerance precedes evolution of resistance (3) and may result in cross-tolerance (26) and collateral sensitivity (27) Figure 3), consistent with the lack of tolerance response at the proteome level. Interestingly, we found colonies in tolerance assays with FOS (fosfomycin), which upon re-testing by MIC displayed an elevated level of resistance and are likely spontaneous mutants ( Supplementary Figure 4), a phenomenon frequently described for this antibiotic (29).…”
Section: Downloaded Fromsupporting
confidence: 80%
“…ST131 spreads between mother-infant pairs [28] likely via an oro-faecal transmission route [29], and such colonisation of infants can last for long periods [30]. Consequently, AMR gene screening can inform on treatment strategies [31] and the effect of antibiotics on microbiomes [32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nitrofurantoin stimulates the production of reactive oxygen species (ROS) ( Garcia Martinez et al, 1995 ) that can facilitate the entry of aminoglycosides and subsequent bacterial killing ( Ezraty et al, 2013 ). Furthermore, aminoglycosides have collateral sensitivity with many antibiotics, nitrofurantoin has also been reported to be collateral sensitivity with tigecycline, mecillinam and protamine, therefore, whether nitrofurantoin has synergistic sensitivity with amikacin is also very much studied ( Suzuki et al, 2014 ; Pal et al, 2015 ; Roemhild et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%